The size and growth of firms: new evidence on law of proportionate effect from Asia. Issue 1 (10th January 2020) - Yadav, Inder Sekhar; Pahi, Debasis; Goyari, Phanindra
Abstract : Purpose: This paper aims to investigate the relationship between firm size and growth under the framework of Law of Proportionate Effect (LPE) for Asian firms. Design/methodology/approach: An unbalanced panel data for about 12, 001 unique non-financial listed and active firms from 1995 to 2016 for 12 industrial and emerging Asian economies was examined. Total assets and net sales were used as size variables. Firm-specific variables such as return on equity, leverage and liquidity ratio were used along with macroeconomic variables such as GDP growth and two financial development indicators. The fixed effects and random effects approach were used to estimate the dynamic growth model after taking into account econometric issues such as correlation between the cross-country-specific error component and the regressors and heteroscedasticity. Findings: The estimated coefficient of firm size was found to be always significant and negative rejecting the Gibrat's law for Asian firms confirming that the small-sized firms are growing faster than larger-sized firms. Also, the persistence of growth coefficient suggested that a positive persistence of firm growth does not exist for the selected Asian firms. Gibrat's LPE was also rejected across small, medium- and large-sized companies. For the aggregate sample, the coefficient of leverage was found to be negative and significant, whereas liquidity ratio, GDP growth, banking sector and stock market variables are found to have positive and significant relationship with growth of firms. For individual economies, a mix of positive and negative (significant and insignificant) estimated coefficient was observed. Practical implications: At macro-level, the examination of firm growth is likely to have significant policy implications for the regulators and various government agencies as firm growth may increase economic activity in general and employment opportunities in particular. The policymakers can control economic and employment activity by designing specific firm growth policies. At micro-level, the study will have significant implications for managerial decision-making. Originality/value: To the best of the authors' knowledge, this is one of the first studies to test the validity of Gibrat's LPE for large Asian economies and firms using recent data under a dynamic growth framework using firm-specific and macroeconomic variables. Also, persistence of growth of firms under LPE (that growth does not persist from one period to the next) is uniquely examined for Asian firms.